2011
DOI: 10.1016/j.biotechadv.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Designs from the deep: Marine organisms for bone tissue engineering

Abstract: Current strategies for bone repair have accepted limitations and the search for synthetic graft materials or for scaffolds that will support ex vivo bone tissue engineering continues. Biomimetic strategies have led to the investigation of naturally occurring porous structures as templates for bone growth. The marine environment is rich in mineralizing organisms with porous structures, some of which are currently being used as bone graft materials and others that are in early stages of development. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 87 publications
0
41
0
6
Order By: Relevance
“…43 Poor results have been also reported when hydroxyapatite granules (Pro Osteon 200™) were used around porous coated metal implants. 7 The results showed that the grafted implants were largely encapsulated in fibrous tissue and the addition of concentrated autologous bone marrow did not change the outcome.…”
Section: Animal Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…43 Poor results have been also reported when hydroxyapatite granules (Pro Osteon 200™) were used around porous coated metal implants. 7 The results showed that the grafted implants were largely encapsulated in fibrous tissue and the addition of concentrated autologous bone marrow did not change the outcome.…”
Section: Animal Studiesmentioning
confidence: 97%
“…Several marine species produce mineralized structures within their anatomy that resembles the human bone. 7 Examples of such species include sponges (Porifera), red algae (Rhadophyta), corals (Cnidarians) and a range of other organisms like snails (Mollusca), starfish (Echinodermata) etc. 7 Among such marine derived biomaterials, corals are one of the most studied in the field of bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goniopora adalah jenis yang paling banyak diekspor setelah Scleractinia (Wabnitz et al 2003). Gabungan antara rangka CaCO 3 dan interkonektivitas antar pori, menjadikan koral potensial sebagai bahan pengganti tulang (Clarke et al 2011). Penelitian sebelumnya menyebutkan bahwa koral kurang sesuai untuk beberapa aplikasi biomedis karena tingkat disolusinya lebih cepat dan memiliki kestabilan struktur yang lemah sehingga menimbulkan reaksi inflamasi ketika dijadikan implan (Silva et al 2012;Correlo et al 2011;Yoo, Park, and Lee 2015).…”
Section: Pendahuluanunclassified
“…Marine sources are novel in this field. Aquatic living organisms such as Coral, Nacre and Cuttlefish have been used in order to enhance bone regeneration recently [16,17] . Cuttlebone (CB) is the hard internal structure of cuttlefish consists of crystals of calcium carbonate (Aragonite) which plays essential role in protecting organism vital organs and act as a floating tank besides.…”
Section: Introductionmentioning
confidence: 99%